The dietary compound luteolin inhibits pancreatic cancer growth by targeting BCL-2. Issue 5 (17th May 2018) - Li, Zhimei; Zhang, Yiyuan; Chen, Lixia; Li, Hua
Abstract : Luteolin, a bioactive flavonoid from celery ( Apium graveolens ), has been rationally proved to trigger SW1990 cells to apoptosis by targeting BCL-2, and may serve as a potential agent for this cancer therapy. Abstract : Overexpression of the prosurvival protein BCL-2 contributes to malignant cell initiation, progression and resistance to treatment. Agents that function as its natural antagonists targeting BCL-2 must provide therapeutic benefit. In SW1990 pancreatic cancer cells, amplified BCL-2 was observed, which was believed to offer advantages for malignant cell survival and lead to poor patient outcome. Using structure-based virtual ligand screening, luteolin was found to be a natural small-molecule inhibitor of BCL-2, which exhibited dose–response proapoptosis activity in a BCL-2 dependent manner in vitro . The cellular thermal shift assay (CETSA) and notably competitive binding assay by the microscale thermophoresis (MST) method provided the evidence that this flavonoid directly bound to BCL-2. Mechanistic studies revealed that luteolin (compound1 ) displaced BAX from the hydrophobic cleft of BCL-2, allowing mitochondrial permeabilization, and inducing SW1990 cancer cells to die. Meanwhile, luteolin represented significant tumor growth inhibition in an SW1990 xenograft model. Collectively, luteolin is rationally proved to trigger SW1990 cells to apoptosis by targeting BCL-2, and may serve as a potential agent for this cancer therapy.